2012
DOI: 10.1523/jneurosci.0110-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Functional Properties of Primary and Posteromedial Visual Area of Mouse Neocortex

Abstract: Visual input provides important landmarks for navigating in the environment, information that in mammals is processed by specialized areas in the visual cortex. In rodents, the posteromedial area (PM) mediates visual information between primary visual cortex (V1) and the retrosplenial cortex, which further projects to the hippocampus. To understand the functional role of area PM requires a detailed analysis of its spatial frequency (SF) and temporal frequency (TF) tuning. Here, we applied two-photon calcium im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
98
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(115 citation statements)
references
References 49 publications
15
98
2
Order By: Relevance
“…However, approximately half as many neurons responded to the NC as to the FC or QC (Figure 2E; V1 p<0.05 FC/QC vs. NC; FC: 40%; QC: 38%; NC: 22%; Tukey’s HSD), likely due to the fact that in untrained mice, fewer V1 neurons are responsive to the oblique orientation of the NC (135°) vs. the cardinal orientation of the FC (0°; Roth et al, 2012). …”
Section: Resultsmentioning
confidence: 99%
“…However, approximately half as many neurons responded to the NC as to the FC or QC (Figure 2E; V1 p<0.05 FC/QC vs. NC; FC: 40%; QC: 38%; NC: 22%; Tukey’s HSD), likely due to the fact that in untrained mice, fewer V1 neurons are responsive to the oblique orientation of the NC (135°) vs. the cardinal orientation of the FC (0°; Roth et al, 2012). …”
Section: Resultsmentioning
confidence: 99%
“…In place of the ordered maps of orientation seen in cat and monkey, the distribution of orientation preferences in rodent V1 appears to be essentially random [1][3]. This “salt-and-pepper” arrangement in the rodent must reflect differences in the wiring of superficial layer neurons in rodents compared to cat and monkey.…”
Section: Introductionmentioning
confidence: 88%
“…But the lesioning techniques used in these studies did not afford the spatial resolution for linking the behavioral deficit unequivocally to specific areas, a problem that will likely be overcome by optogenetic approaches (Lien and Scanziani 2013). Recently, significant progress was made by two-photon imaging of calcium transients in upper layer neurons of multiple areas in mouse visual cortex (Andermann et al 2011;Marshel et al 2011;Roth et al 2012). These recordings showed that tuning to high spatial frequency was more common in LI than in AL, RL and AM, which are more selective for high temporal frequency and the direction of motion.…”
Section: Dorsal and Ventral Processing Streamsmentioning
confidence: 99%